2020
DOI: 10.1103/physrevd.102.054512
|View full text |Cite
|
Sign up to set email alerts
|

Moments of nucleon isovector structure functions in 2+1+1 -flavor QCD

Abstract: We present results on the isovector momentum fraction, hxi u−d , helicity moment, hxi Δu−Δd , and the transversity moment, hxi δu−δd , of the nucleon obtained using nine ensembles of gauge configurations generated by the MILC Collaboration using 2 þ 1 þ 1-flavors of dynamical highly improved staggered quarks. The correlation functions are calculated using the Wilson-Clover action, and the renormalization of the three operators is carried out nonperturbatively on the lattice in the RI 0-MOM scheme. The data hav… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 53 publications
(70 reference statements)
5
23
0
Order By: Relevance
“…(4.1), couples to the nucleon, all its excitations and multiparticle states with the same quantum numbers. Previous lattice calculations have shown that these ESC can be large [16,[33][34][35]. The strategy to remove these artifacts in this work is the same as described in ref.…”
Section: Controlling Excited State Contaminationmentioning
confidence: 99%
See 4 more Smart Citations
“…(4.1), couples to the nucleon, all its excitations and multiparticle states with the same quantum numbers. Previous lattice calculations have shown that these ESC can be large [16,[33][34][35]. The strategy to remove these artifacts in this work is the same as described in ref.…”
Section: Controlling Excited State Contaminationmentioning
confidence: 99%
“…The strategy to remove these artifacts in this work is the same as described in ref. [16]: reduce ESC by using smeared sources in the generation of quark propagators and then fit the data at multiple source-sink separations τ using the spectral decomposition of the correlation functions (eqs. (5.1) and (5.2)) keeping as many excited states as possible without overparameterizing the fits.…”
Section: Controlling Excited State Contaminationmentioning
confidence: 99%
See 3 more Smart Citations